Fenomenologia e crimes contra a humanidade = Phenomenology and crimes against humanity - Cittadino, Rodrigo Cerveira (Revista Eletrônica de Direito Penal e Política Criminal, 2018)
The present article aims to study crimes against humanity from a phenomenological perspective, which refers to a philosophical movement that looks for the defining essence of social concepts and phenomena. In this regard, we expose some theories which have addressed the characteristics that singularize crimes against humanity, or, in other words, that differentiate them from any other legal or extralegal notion which may seem indistinguishable from them. In order to achieve this outcome, this work is divided into three parts. Firstly, we draft a brief history of crimes-against-humanity terminology and corresponding rules, not only because an analysis of these criminal norms requires knowing the various international instruments which address them, but also because a philosophical investigation about the meanings conferred to this concept may get inspiration from an inquiry about how it has been used over time. Secondly, we examine the legal content of crimes against humanity, enumerating their normative elements according to the relevant internacional treaties and international tribunals’ jurisprudence. Thirdly and lastly, we deal with the phenomenological approach to the abovementioned crimes, which is the purpose of this article.